Kontribusi Pemberian Insentif Dalam Meningkatkan Kinerja Guru Di MIS Budaya Langkat Desa Tanjung Ibus Kecamatan Secanggang - Linda Yunita (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The official notification regarding the receipt of incentive funds is based on information from the head of the madrasah, it seems that this incentive is no longer given to teachers who previously received it. According to the head of the madrasah, it seems that incentive assistance has been eliminated because all the schools that previously received it no longer receive it. It is possible that this assistance will be diverted into functional allowances for teachers. The incentives issued to teachers are usually given in the range of once every three months to four months in the amount of one million two hundred and fifty thousand rupiah. Data collection methods include library research, observation, questionnaires and interviews. Data analysis techniques by collecting information in the field through observation, interviews, document research, documentation of each research activity and literature study. Reducing data, presenting data, and The final stage is to provide conclusions. The research conclusion is that incentives for teachers have a good contribution to teacher performance, especially to teaching enthusiasm. The incentives received by teachers will encourage work enthusiasm so that the quality of work increases and the results will be maximized. According to the head of the madrasah, incentives can be a motivation in educating because teachers get additional honorarium from what they have received so far. Even though teachers are sincere in educating, if there is an incentive, of course as an ordinary human being they will be happy and more enthusiastic in providing learning.